2011
DOI: 10.1063/1.3563060
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of x-ray specular reflectometry to the oxygen-induced magnetic properties in Pt/Co/AlOx

Abstract: Two key parameters were analyzed in Si/SiO/Pt/Co/AlOx: the oxidation time of the Al layer resulting in AlOx, and the ex situ annealing temperatures varied in the 15 and 55 s and 20, 300, and 450  °C ranges, respectively. For intermediate annealing temperatures (∼300  °C), the quantitative analysis of specular reflectometry data shows that the progressive oxidation of layers by increasing the oxidation time goes along with an improvement of the homogeneity of the alumina layer. This outcome casts new light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…47 This explains why CoO is induced for as-grown samples, and that annealing favors the appearance of Co 3 Pt. Now, we discuss the room temperature magnetic properties of the system at the light of our structural results: 23,26 (i) For as-deposited samples and increasing t Ox , a crossover between Pt/Co/Al/AlO x and Pt/Co-CoO x /AlO x stacks is observed. In particular, t à Ox ¼ 40 s appears to be a reasonable oxidation time for obtaining a highquality AlO x layer (both maximized Th and q), but with marked roughnesses for the different layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 This explains why CoO is induced for as-grown samples, and that annealing favors the appearance of Co 3 Pt. Now, we discuss the room temperature magnetic properties of the system at the light of our structural results: 23,26 (i) For as-deposited samples and increasing t Ox , a crossover between Pt/Co/Al/AlO x and Pt/Co-CoO x /AlO x stacks is observed. In particular, t à Ox ¼ 40 s appears to be a reasonable oxidation time for obtaining a highquality AlO x layer (both maximized Th and q), but with marked roughnesses for the different layers.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of a ferromagnetic/antiferromagnetic (Co-CoO x ) coupling is also observed in the low temperature regime of magnetic properties. 26,48 In addition, Rodmacq et al 23 found that the amplitude of the Hall resistance considerably decreases for the longest oxidation times. 23 We show here that it is explained by the appearance of CoO x .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tunneling properties and the stability of the magnetic tunneling junctions strongly depend on the structural and magnetic arrangement of the electrodes and barrier material. Several studies demonstrated an influence of nonmagnetic metals (NM) cover layers on the interfacial PMA of Co [10,11,12,13]. It has been recognized, that the effect is determined by the orbital moment anisotropy of Co and could be modified by an interface hybridization of the NM layer (e.g., its d or p orbitals) with Co 3d orbitals [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%